Corporate Governance Perception Index and Firm Performance in Indonesia - Arif Budi Satrio (Media Ekonomi dan Manajemen, 2022)
The unique business environment and inconclusive findings make it interesting to conduct investigations related to corporate governance and performance in Indonesia. The investigation is carried out on all firms on the Indonesia Stock Exchange, which The Indonesian Institute for Corporate Governance has surveyed for almost two decades (2001 to 2019). The test results find a significant relationship between corporate governance and firm performance. This study underscores the importance of stakeholders in making a collective contribution to the firm. A series of tests have been carried out to validate these findings, and the results remain robust. This finding has important contributions and implications for regulators and firms, especially in developing countries.